Prevalence of Anemia, Iron Level, Total Iron Binding Capacity Level, and Body Mass Index of Medical Students Living in Hostels in South India - Senthilkumar, Kalimuthu; Kalaiyazhagan, Magendran; Lalamiya Abdul Rahiman, Baba; Ravichandran, Shanmugasundaram (The Journal of Experimental Life Science, 2024)
Studies have evidenced that hostel-staying medical students are at increased risk for anemia due to improper diet and long periods of studies that ultimately affect their performance. The nature of medical education, student efforts, and stress also raise the risk of anemia. The objective of this study is to find out the prevalence of anemia in medical students and iron levels, total iron binding capacity (TIBC) levels, and body mass index (BMI) in residing medical students in the hostel. This study is a descriptive cross-sectional study conducted at the Swamy Vivekanandha Medical College Hospital and Research Institute (SVMCHRI). The Institutional Ethical Committee (IEC) was obtained from IEC-SVMCHRI. The total number of students who participated in this study was 115 first-year medicine students (female = 76, male = 39) aged 18-24 years and were boarded in the hostel. Samples were collected after obtaining informed consent from students. Demographic parameters such as name, age, sex, and anthropometric parameters including weight, height, and BMI were recorded. Haemoglobin (Hb) was analyzed by a cell counter analyzer, iron levels, and TIBC levels were measured by a semi-autoanalyzer, and a blood smear study was performed. Anemia prevalence was higher in females than males; therefore, statistical analysis for male and female associations was observed through the Chi-squared test. The Hb cut-off followed the anemia classification per the World Health Organization (WHO). Overall, students had severe anemia (0.9%), moderate (8.7%), and mild (26.1%) anemia in hostels studying medicine. Females had a higher prevalence of anemia than males.  The comparison of Hb, iron levels, and TIBC levels between men and women was highly significant: Hb 14.93 and 11.85 g.dL-1 in men vs. women (P<0.001); iron levels 122.07 and 77.5289 µg.dL-1 in men vs. women (P<0.001); and TIBC levels 323.02 and 349.92 µg.dL-1 in men vs. women (P<0.008), consecutively. BMI was not significant between male and female associations. Overall, 18 participants had microcytic and hypochromic anemia in the blood smear study. This research finding concludes that the anemia prevalence is more common in female medical students with a tendency to microcytic and hypochromic anemia. Therefore, they may suffer from anemia due to nutritional deficiencies and benefit from iron supplementation. Keywords: Anemia, Iron, Hemoglobin, Microcytic and Hypochromic, Total Ion Binding Capacity.